HEGEMONI KEKUASAAN DALAM NOVEL ANIMAL FARM KARYA GEORGE ORWELL (TEORI GRAMSCI) - Sasanti Silvya Putri; Mutia Hesti Istiqomah; Kuncoro, Nayla Amara; Susanto, Dwi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This research aims to elucidate the hegemony of power as proposed by Gramsci in George Orwell's novel Animal Farm. The study is limited to practices of hegemony such as information manipulation, propaganda, changing rules, historical erasure, control of education, and the creation of a common enemy, without discussing other literary elements outside this theory. This research uses a descriptive qualitative method employing the note taking technique. The researcher observed the entire content of the novel, then recorded and classified data related to Gramsci's theory of hegemony. The resulting data consisted of phrases, clauses, and sentences containing elements of Gramscian power hegemony, specifically those depicting practices of ideological power. The results of this study show forms of hegemony evident in the dominant characters, particularly Napoleon and the group of pigs, who build and maintain power through ideological strategies that create consensus among the other animals. This finding demonstrates that propaganda and ideological control are ultimately more effective than physical force in maintaining domination.